“Actividades lúdicas para el desarrollo del autoconcepto en los niños de Educación Inicial” - Tipán Vega, Tatiana Guadalupe (2024)
The present research the identified problem is the lack of utilitarian recreational activities for teachers in the development of self-concept in children of Initial Education, in response to this the following objective is proposed: "Design recreational activities for the development of self-concept in children of Initial Education", The methodology used for the research documents a mixed approach, and for data collection it was the survey technique carried out on the teachers and participant observation on the children in early education; managing to determine that there are gaps in issues related to self-concept. After investigating and learning about the different theories and perspectives of teachers, the need for an intervention is concluded, with the necessary strategies and knowledge to adequately support the emotional and social growth of their students. The findings highlight the critical need to undertake educational actions that contribute to strengthening self-concept in childhood. Therefore, the implementation of a series of recreational activities specially designed to overcome the observed limitations is suggested.